The Assessment of Dimension Absorptive Capacity on Innovation Performance and Small Business Performance - Wiwoho, Gunarso (P4M STIE Putra Bangsa, 2016)
This study aims to examine the role of the absorptive capacity dimension in improving innovation performance and small business performance. The sample used as many as 35 businesses in the business sector of handy crafts. The collected data were analyzed using path analysis and processed with SPSS software version 24.0. The results showed that all hypotheses were accepted. The absorptive capacity dimension consists of potential absorptive capacity and absorptive capacity, both of which are able to have a positive influence on the performance of innovation and the performance of small businesses. But realized absorptive capacity can have a greater influence on innovation and small business performance than potential absorptive capacity.